Supply Chain CSR Image Challenges â€“ A Study on Bangladesh Clothing Industry - Ehsanul Huda Chowdhury; Agneta SundstrÃ¶m; Akmal S. Hyder (International Journal of Supply Chain Management, 2016)
This paper provides a deep insight into the corporate social responsiblity (CSR) image scenariao of the Bangladesh suppliers as well as identifies the challanges for building a positive supply chain (SC) CSR image for the suppliers of Bangladesh clothing industry. The contribution of this paper is that it improves knowledge of SC CSR image from the suppliers' as well as buyers' perspective. The paper also make suggestions regarding improvment of suppliers' CSR image that can influence the improvement of SC CSR image